Peningkatan Hasil Belajar Siswa pada Tema 7 Perkembangan Teknologi Melalui Model Pembelajaran Problem Based Learning di Kelas III SDN Karangreja 01 Kabupaten Brebes - Jumi Astiti; Ervina Eka Subekti; Kuswandari Kuswandari (Universitas Pendidikan Mandalika, 2021)
The purpose of this study was to improve student learning outcomes on theme 7 of technological development through a problem based learning model in class III SDN Karangreja 01 Brebes Regency. This research method used classroom action research which consists of three cycles. The subjects of this study were students in class III, amounting to 22 people. The data collection technique in this study was through test and non-test methods, while the data analysis technique used descriptive analysis. The results of this study indicate that the learning outcomes of students in the first cycle get an average score of 62.0, in the second cycle the average score is 67.50 and in the third cycle the average score is 82.50. So the conclusion of this study is that through the Problem Based Learning model, it can improve student learning outcomes.